2014
DOI: 10.1038/bjc.2014.434
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Mediterranean diet and other dietary patterns and breast cancer risk: case–control EpiGEICAM study

Abstract: Background:Although there are solid findings regarding the detrimental effect of alcohol consumption, the existing evidence on the effect of other dietary factors on breast cancer (BC) risk is inconclusive. This study aimed to evaluate the association between dietary patterns and risk of BC in Spanish women, stratifying by menopausal status and tumour subtype, and to compare the results with those of Alternate Healthy Index (AHEI) and Alternate Mediterranean Diet Score (aMED).Methods:We recruited 1017 incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
201
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(224 citation statements)
references
References 41 publications
(56 reference statements)
15
201
3
5
Order By: Relevance
“…In some studies, there was no association found between breast cancer risk and the 'Cereals/Milk/Dairy' DP, 'Vegetable' DP and 'Prudent' DP rich in low-fat dairy products, juices, whole grains, vegetables and fruit. 13,20,21 The differences in these associations could result from differences in the study designs, study populations, secular trends in food supply or different definitions of 'Prudent/Healthy' diet and characteristics for their foods. 19 In these studies, the 'Processed & fast food' DP was characterized by a higher frequency of consumption of alcoholic drinks and processed food such as fast food, instant soups and canned goods, which increased the risk of breast or lung cancers almost 2 times, but this relation was weaker and disappeared after the adjustment for many confounders.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, there was no association found between breast cancer risk and the 'Cereals/Milk/Dairy' DP, 'Vegetable' DP and 'Prudent' DP rich in low-fat dairy products, juices, whole grains, vegetables and fruit. 13,20,21 The differences in these associations could result from differences in the study designs, study populations, secular trends in food supply or different definitions of 'Prudent/Healthy' diet and characteristics for their foods. 19 In these studies, the 'Processed & fast food' DP was characterized by a higher frequency of consumption of alcoholic drinks and processed food such as fast food, instant soups and canned goods, which increased the risk of breast or lung cancers almost 2 times, but this relation was weaker and disappeared after the adjustment for many confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Diet can also be a risk factor for many chronic diseases, and some food intake and dietary habits are considered as a high risk for cancer development (Castello´ et al, 2014). However, to our knowledge, there is no research study that supports the association between a specific diet and TNBC development.…”
Section: Tnbc and Dietmentioning
confidence: 97%
“…Moreover, a high cholesterol diet has been shown to induce angiogenesis and accelerate mammary tumor growth in a mouse model of triple negative breast cancer (Castellō et al, 2014). Interestingly enough, Castellò et al have highlighted the benefits of a diet rich in fruits, vegetables, legumes, oily fish and vegetable oils to prevente all BC subtypes, and particularly triple-negative tumors (Castello et al, 2014).…”
Section: Tnbc and Dietmentioning
confidence: 99%
“…The final session addressed the ten best (i.e., rich in antioxidants) and the ten worst (i.e., rich in animal fat) dietary components, which might prevent or promote cancer. The study dieticians 'recommended patients try to adopt the Mediterranean diet [15].…”
Section: Intervention Groupmentioning
confidence: 99%